2013
DOI: 10.4085/1062-6050-48.2.02
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Experimental Knee-Pain Model Affects Perceived Pain and Movement Biomechanics

Abstract: Context: Knee injuries are prevalent, and the associated knee pain is linked to disability. The influence of knee pain on movement biomechanics, independent of other factors related to knee injuries, is difficult to study and unclear.Objective: (1) To evaluate a novel experimental knee-pain model and (2) better understand the independent effects of knee pain on walking and running biomechanics.Design: Crossover study. Setting: Biomechanics laboratory.Patients or Other Participants: Twelve able-bodied volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
35
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 47 publications
6
35
1
Order By: Relevance
“…30 We also reported reduced peak ankle plantar-flexion angles during running. The primary difference between our study and previously mentioned studies 30,54 is the chronicity of pain in our participants. This might have influenced their response to pain by dampening the effect of the RSLS protocol, as can be seen in the relatively smaller magnitude of changes in pain we found (0.99-1.50 cm) compared with previous investigators (2.58 cm by Henriksen et al 54 and 4.29 cm by Seeley et al 30 ).…”
Section: Kinematicsmentioning
confidence: 87%
See 4 more Smart Citations
“…30 We also reported reduced peak ankle plantar-flexion angles during running. The primary difference between our study and previously mentioned studies 30,54 is the chronicity of pain in our participants. This might have influenced their response to pain by dampening the effect of the RSLS protocol, as can be seen in the relatively smaller magnitude of changes in pain we found (0.99-1.50 cm) compared with previous investigators (2.58 cm by Henriksen et al 54 and 4.29 cm by Seeley et al 30 ).…”
Section: Kinematicsmentioning
confidence: 87%
“…53 Authors of experimental knee-pain studies have reported few kinematic changes, including decreased knee-flexion 54 and ankle plantar-flexion 30 angles during walking and decreased plantar-flexion and hip-adduction angles during running. 30 We also reported reduced peak ankle plantar-flexion angles during running. The primary difference between our study and previously mentioned studies 30,54 is the chronicity of pain in our participants.…”
Section: Kinematicsmentioning
confidence: 99%
See 3 more Smart Citations